Analisis Kualitas Air Dan Daya Tampung Beban Pencemaran Sungai Bedadung - Maharika, Mayang; ., Yushardi; ., Sudarti (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purpose of this research article is to find out the water quality and capacity to carry pollution loads in the Bedadung River. The quality of river water in an area is greatly influenced by human activities. Therefore, it must be balanced with public awareness in preserving the river environment so that the quality of river water is maintained. Water quality is the general condition of water that describes the chemical, physical and biological content of water with the help of certain references. Water quality is usually influenced by the pollutant load entering the water body. The pollutant load itself is the amount of pollutant substances present in the water. In a body of water there is a limit to the amount of pollutant load that can be accepted by its designated class or what is generally referred to as the maximum pollutant load.